2012
DOI: 10.1136/jclinpath-2012-200797
|View full text |Cite
|
Sign up to set email alerts
|

Trends of stage, grade, histology and tumour necrosis in renal cell carcinoma in a European centre surgical series from 1984 to 2010

Abstract: In contrast to data from Australia but similar to data from US cohorts, a statistically significant stage migration towards small RCCs was observed in this European cohort. Significant changes in tumour grade, histological subtype and TN were also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The male/female ratio may be different in the studies. While this ratio was 1.9 in a study from China (Chen et al, 2009), was 1.39 in a study from Austria (Pichler et al, 2012). We found the male/female ratio was 2.13 in the patients with RCCs.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The male/female ratio may be different in the studies. While this ratio was 1.9 in a study from China (Chen et al, 2009), was 1.39 in a study from Austria (Pichler et al, 2012). We found the male/female ratio was 2.13 in the patients with RCCs.…”
Section: Discussionmentioning
confidence: 77%
“…The proportion of grade II tumours was between 43 and 61.5%. There is an increasing representation of grade III and IV tumours over time, from 12.7 to 20.3% and decreasing the proportion of grade I tumours from 32 to 14.8% in an analysis of 2,739 patients (Pichler et al, 2012). Additionally, the authors reported that there was a significant increase of grade III tumours over time, from 17.6 to 30.8% and decreasing proportion of grade I tumours from 16.2 to 7.1% (Doeuk et al, 2010).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations